2017
DOI: 10.1002/pssc.201600193
|View full text |Cite
|
Sign up to set email alerts
|

Cu2(Sn1−xGex)S3 solar cells prepared via co‐evaporation and annealing in germanium sulfide and sulfur vapor

Abstract: Cu2Sn1−xGexS3 (CTGS) thin films were prepared by co‐evaporation of Cu, Sn, and S to form Cu2SnS3 (CTS) precursors, which were then annealed at 570 °C in an atmosphere composed of N2, GeS2, and S vapor. The films were then used to fabricate photovoltaic cells with the structure glass/Mo/CTGS/CdS/ZnO:Al/Al. A cell with a film composition of Cu2(Sn0.86Ge0.14)S3 fabricated from slightly Cu‐rich CTS (Cu/Sn = 2.07) exhibited a conversion efficiency of 3.4% and an open‐circuit voltage of 0.29 V. The band gap based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Recently, Araki et al have reported the band-gap energies of Cu 2 SnS 3 (0.92 eV) and Cu 2 GeS 3 (1.51 eV). 10) They also reported the synthesis and characterization of Cu 2 -(Ge x Sn 1−x )S 3 solid solution samples. 24) They prepared Cu 2 (Ge x Sn 1−x )S 3 powder from the elemental raw materials Cu, Sn, Ge, and S. They sealed them in quartz tubes evacuated to the order of 10 −3 Pa and then heated them at appropriate temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Araki et al have reported the band-gap energies of Cu 2 SnS 3 (0.92 eV) and Cu 2 GeS 3 (1.51 eV). 10) They also reported the synthesis and characterization of Cu 2 -(Ge x Sn 1−x )S 3 solid solution samples. 24) They prepared Cu 2 (Ge x Sn 1−x )S 3 powder from the elemental raw materials Cu, Sn, Ge, and S. They sealed them in quartz tubes evacuated to the order of 10 −3 Pa and then heated them at appropriate temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies on the optical properties and electronic structures of Cu 2 SnS 3 , Cu 2 GeS 3 , and their solid solution. The band gap energy of monoclinic Cu 2 GeS 3 was reported to be in the range of 1.5-1.6 eV by Araki et al 10,21) and 1.5 eV by Tsuji et al 22) In this study, Cu 2 SnS 3 , Cu 2 GeS 3 , and Cu 2 (Ge x Sn 1−x )S 3 solid solution samples were prepared from element powders. Their crystal structures were refined by Rietveld refinement using XRD data.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This kind of profile of SSSe ratios at the GI and GB is applicable to other kinds of polycrystalline solar cells, such as Cu 2 Zn(Ge, Sn)(S, Se) 4 [25][26][27][28] and Cu 2 (Ge, Sn)(S, Se) 3 . [29][30][31][32][33] We also can design the depth profiles of the energy levels of the VBM and CBM in Cu 2 Zn(Ge, Sn)(S, Se) 4 and Cu 2 (Ge, Sn)(S, Se) 3 absorber layers by controlling the depth profile of the Ge/(Ge+Sn) and SSSe ratios. The VBM levels of the Cu 2 Zn(Ge x Sn 1-x )S 4 [Cu 2 Zn(Ge x Sn 1-x )Se 4 ] 27) and Cu 2 (Ge x Sn 1-x )S 3 [Cu 2 (Ge x Sn 1-x )Se 3 ] 33) systems do not change significantly with an increasing Ge/(Ge+Sn) ratio, x.…”
Section: Quantitative Analyses Of Vbm and Cbm Levels Of Cigsse Systemmentioning
confidence: 99%
“…To date, several studies have investigated sulfurization for CTGS thin films. [13][14][15] Nevertheless, controlling the atomic ratio is difficult because GeS tends to re-evaporate more easily than SnS during sulfurization owing to their different vapor pressures. 16,17) In this study, the relationship of sulfurization to the crystal quality of CTGS thin films deposited by low-temperature co-evaporation was investigated to realize compositionally graded CTGS solar cells.…”
Section: Introductionmentioning
confidence: 99%